The private life of spiders - Hillyard, Paul (London : New Holland, 2011)
Presents an illustrated guide to the anatomy, behavior, social organization, reproduction, hunting techniques, and web construction of a variety of spiders from around the world.
Ch. 1. Background to spiders -- ch. 2. Spiders that hunt -- ch. 3. Spiders that build webs -- ch. 4. Tarantulas and trapdoor spiders -- ch. 5. The silk factory -- ch. 6. Mating and breeding -- ch. 7. The use of venom -- ch. 8. Social spiders -- ch. 9. Spiders and humans -- Glossary -- Further reading -- Index.
Includes bibliographical references (page 155) and index.
Keywords: Spiders; Spiders -- Pictorial works